ER, Mitochondria, and ISR Regulation by mt‐HSP70 and ATF5 upon Procollagen Misfolding in Osteoblasts - Laura Gorrell; Elena Makareeva; Shakib Omari; Satoru Otsuru; Sergey Leikin (Advanced Science, 2022)
Abstract Cellular response to protein misfolding underlies multiple diseases. Collagens are the most abundant vertebrate proteins, yet little is known about cellular response to misfolding of their procollagen precursors. Osteoblasts (OBs)—the cells that make bone—produce so much procollagen that it accounts for up to 40% of mRNAs in the cell, which is why bone bears the brunt of mutations causing procollagen misfolding in osteogenesis imperfecta (OI). The present study of a G610C mouse model of OI by multiple transcriptomic techniques provides first solid clues to how OBs respond to misfolded procollagen accumulation in the endoplasmic reticulum (ER) and how this response affects OB function. Surprisingly, misfolded procollagen escapes the quality control in the ER lumen and indirectly triggers the integrated stress response (ISR) through other cell compartments. In G610C OBs, the ISR is regulated by mitochondrial HSP70 (mt‐HSP70) and ATF5 instead of their BIP and ATF4 paralogues, which normally activate and regulate ISR to secretory protein misfolding in the ER. The involvement of mt‐HSP70 and ATF5 together with other transcriptomic findings suggest that mitochondria might initiate the ISR upon disruption of ER‐mitochondria connections or might respond to the ISR activated by a yet unknown sensor.